EFFICACY OF VEGETABLE OILS AND BOTANICALS IN THE CONTROL OF PULSE BEETLE ( Callosobruchus chinensis L.) IN STORED PIGEONPEA - P. RAGHU RAMI REDDY, B. DILEEP KUMAR and (The Journal of Research, PJTSAU, 2017)
Pigeonpea or Redgram (Cajanus cajan L.) is an important pulse crop in India and is the main source of protein for vegetarians. The pulse seeds suffer a great damage during storage due to insect attack. Among the insect pests attacking stored products the pulses beetle Callosobruchus chinensis L. is a serious one. This insect has been reported from thePhilippines, Japan, Indonesia, Sri Lanka, Myanmar and India. It is a notorious pest of chickpea, pigeonpea, mung, motor, peas, cowpea and lentil (Aslam et al., 2002). Pulse beetle being an internal feeder connot be controlled with insecticides. It is also not advisable to mix insecticides with food grains. Callosobruchus (l) attacking Vigna species was also tested against several oils. Castor oil at 8 ml. kg-1 provided complete protection against Callosobruchus (Singh et al., 1978). Palm and coconut oils at 4 mlkg-1 were the most effective protectants of chickpea seeds against C. chinensis for 3 months of storage followed by groundnut, rapeseed and mustard oils. Sesame, sunflower and soybean oils were consideredinferior to the others (Singh et al., 1990). Neem seed oil showed 100% control of C. chinensis for 5 months when applied at 10 ml. kg-1 chickpea seeds (Das, 1987).